Acute Neuroinflammatory Response in the Substantia Nigra Pars Compacta of Rats after a Local Injection of Lipopolysaccharide - Yazmin M. Flores-Martinez; Manuel A. Fernandez-Parrilla; Jose Ayala-Davila; David Reyes-Corona; Victor M. Blanco-Alvarez; Luis O. Soto-Rojas; Claudia Luna-Herrera; Juan A. Gonzalez-Barrios; Bertha A. Leon-Chavez; Maria E. Gutierrez-Castillo; Irma A. Martínez-Dávila; Daniel Martinez-Fong (Journal of Immunology Research)
Models of Parkinson’s disease with neurotoxins have shown that microglial activation does not evoke a typical inflammatory response in the substantia nigra, questioning whether neuroinflammation leads to neurodegeneration. To address this issue, the archetypal inflammatory stimulus, lipopolysaccharide (LPS), was injected into the rat substantia nigra. LPS induced fever, sickness behavior, and microglial activation (OX42 immunoreactivity), followed by astrocyte activation and leukocyte infiltration (GFAP and CD45 immunoreactivities). During the acute phase of neuroinflammation, pro- and anti-inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-4, and IL-10) responded differentially at mRNA and protein level. Increased NO production and lipid peroxidation occurred at 168 h after LPS injection. At this time, evidence of neurodegeneration could be seen, entailing decreased tyrosine hydroxylase (TH) immunoreactivity, irregular body contour, and prolongation discontinuity of TH+ cells, as well as apparent phagocytosis of TH+ cells by OX42+ cells. Altogether, these results show that LPS evokes a typical inflammatory response in the substantia nigra that is followed by dopaminergic neurodegeneration.